2017
DOI: 10.1002/cce2.51
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias in acute coronary syndromes—mechanisms and management

Abstract: Ventricular arrhythmias occur commonly following myocardial infarction and carry important prognostic implications. The mechanisms involved are varied and time-dependent, changing with the evolution of the infarct, and this has implications for the management of both the arrhythmia and the index ischemic insult, which are discussed in this article. Current evidence-based best practice and management guidelines are reviewed, and consideration is given to some of the unique challenges that managing this group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
0
12
0
2
Order By: Relevance
“…After adjusting for several potentially confounding variables, we found that patients with hyperglycemia were at increased risk for developing early VT. Early VT may be triggered by increased sympathetic activity or the inflammatory response to acute ischemic injury, each of which have been shown to be associated with elevated serum glucose levels in patients with AMI [ 31 ]. Inflammatory responses to the acute ischemic insult predominately occur during the first few days after an AMI and are associated with increased resting membrane potential and prolonged action potential duration [ 25 , 29 ], which may contribute to the triggering of early onset VT [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for several potentially confounding variables, we found that patients with hyperglycemia were at increased risk for developing early VT. Early VT may be triggered by increased sympathetic activity or the inflammatory response to acute ischemic injury, each of which have been shown to be associated with elevated serum glucose levels in patients with AMI [ 31 ]. Inflammatory responses to the acute ischemic insult predominately occur during the first few days after an AMI and are associated with increased resting membrane potential and prolonged action potential duration [ 25 , 29 ], which may contribute to the triggering of early onset VT [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated idioventricular rhythm is common in the clinical practice and may result from increasing autonomic stimulation of Purkinje fibers near the ischemic region, thus enhancing automaticity or triggered activity [ 23 ]. Several factors increase the susceptibility of ischemic myocardium to reperfusion arrhythmia, including acidosis, α-adrenergic stimulation, and angiotensin II release [ 24 ].…”
Section: Linical Manifestations Of Ischemia/reperfusion Imentioning
confidence: 99%
“…Although the absolute rates of VT and VF have declined during the era of percutaneous coronary intervention, patients suffering from VT or VF prior to revascularization still have a significantly impaired outcome and are at a higher risk for stent thrombosis. These data may underestimate the true incidence, since prehospital SCD before fibrinolysis or any other interventions were not included in this analysis 35 . In the present study, we modeled a clinical scenario of myocardial ischemia by LAD ligation and demonstrated that intraperitoneal injection of NO 2 -OA 20 min before he ischemic episode sustainably reduced ventricular arrhythmic events specifically in the acute phase after AMI.…”
Section: Discussionmentioning
confidence: 99%